2021
DOI: 10.3389/fnbeh.2021.652636
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Methodological Considerations for the Use of Single Prolonged Stress and Fear Extinction Retention in Rodents

Abstract: Posttraumatic stress disorder (PTSD) is a mental health condition triggered by experiencing or witnessing a terrifying event that can lead to lifelong burden that increases mortality and adverse health outcomes. Yet, no new treatments have reached the market in two decades. Thus, screening potential interventions for PTSD is of high priority. Animal models often serve as a critical translational tool to bring new therapeutics from bench to bedside. However, the lack of concordance of some human clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 197 publications
1
7
0
Order By: Relevance
“…Enhanced anxiety-like behavior and impaired extinction memory are symptoms observed in male rodents subjected to the SPS procedure (Liberzon and Young, 1997;Kohda et al, 2007;Knox et al, 2012aKnox et al, , 2016Noble et al, 2017;Ferland-Beckham et al, 2021). Consistent with previous results, we found that SPS exposure increased anxiety-like behavior and severely impaired extinction of conditioned fear in male rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Enhanced anxiety-like behavior and impaired extinction memory are symptoms observed in male rodents subjected to the SPS procedure (Liberzon and Young, 1997;Kohda et al, 2007;Knox et al, 2012aKnox et al, , 2016Noble et al, 2017;Ferland-Beckham et al, 2021). Consistent with previous results, we found that SPS exposure increased anxiety-like behavior and severely impaired extinction of conditioned fear in male rats.…”
Section: Discussionsupporting
confidence: 92%
“…Prior work indicates that the SPS protocol induces behavioral and physiological phenomena similar to those observed in PTSD patients (Liberzon and Young, 1997;Blechert et al, 2007;Kohda et al, 2007;Glover et al, 2011;Norrholm et al, 2011;Knox et al, 2016). Although the SPS protocol does not impair extinction or increase anxiety-like behavior in female rats (Keller et al, 2015;Mancini et al, 2021), this procedure has been widely used as an animal model of PTSD (Liberzon and Young, 1997;Knox et al, 2016;Souza et al, 2017;Lisieski et al, 2018;Serova et al, 2019;Su et al, 2019;Ferland-Beckham et al, 2021). In addition to increased anxiety and impaired extinction memory consolidation, rats show increased negative hypothalamic-pituitary-adrenal (HPA) feedback (Knox et al, 2012a(Knox et al, , 2016Han et al, 2014;Liu et al, 2016;Noble et al, 2017;Deslauriers et al, 2018) and altered glucocorticoid receptor expression 7 days after SPS exposure (Liberzon et al, 1999;Wang et al, 2009;Knox et al, 2012b;George et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Identifying neurobiological mechanisms via which axis, arousal, and re-experiencing symptoms (Liberzon et al, 1997(Liberzon et al, , 1999Khan and Liberzon, 2004;Kohda et al, 2007;George et al, 2012George et al, , 2015Knox et al, 2012). SPS also is relatively easy to implement and can be adapted in a range of research settings (Ferland-Beckham et al, 2021). However-like many animal models of PTSD-SPS was developed in male animals and the consistent effects observed in these animals are not often observed in female animals (Bowers and Ressler, 2015;Keller et al, 2015;Deslauriers et al, 2018;Pooley et al, 2018a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of the immune system in the pathophysiology of PTSD is unclear, increasing clinical evidence links increased levels of inflammatory cytokines with PTSD [2,[26][27][28]. In our study, we used a well-studied SPS animal model to examine the role of inflammation in the development of PTSD-like behavior after trauma exposure [29][30][31][32]. The delayed onset of impaired fear extinction and increased anxiety-like behavior induced by the SPS protocol [7,11,33] allowed us to examine changes in inflammation prior to the onset of the PTSD-like phenotype.…”
Section: Discussionmentioning
confidence: 99%